(untitled) - Black, Michael (Cambridge, 2000)
This is a short, illustrated account of the world's oldest publishing house, from the publication of the Press's first book in 1584 through to the present day. It emphasizes the constitutional basis of the Press--an essential part of its parent university--and highlights key moments of crisis and change: Richard Bentley's revival in the 1690s, the Victorian renaissance, the rise of modern university publishing, two world wars, the crisis of the 1970s--resolved by Geoffrey Cass' bold reconstruction--and the enterprising printing and publishing developments of the 1990s.
Keywords: Cambridge University Press,University presses,Nhà xuất bản Đại học Cambridge,Sự kiện đại học; History,History,Lịch sử; Cambridge,England,Cambridge,Nước Anh